1977
DOI: 10.1084/jem.145.5.1115
|View full text |Cite
|
Sign up to set email alerts
|

Features of systemic lupus erythematosus in mice injected with bacterial lipopolysaccharides: identificantion of circulating DNA and renal localization of DNA-anti-DNA complexes.

Abstract: After injection of lipopolysaccharides (LPS) in mice, there is first a release of DNA into plasma and secondly an induction of anti-DNA antibodies. The circulating DNA was purified from plasma and physico-immunochemically characterized. This DNA has a similar density to mammalian cellular DNA,is 4--6S insize, and probably represents a mixture of single-stranded DNA (SSDNA) and double-stranded DNA (DSDNA) or DSDNA with some single-stranded regions. This purified DNA was shown to react with anti-DNA antibodies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
59
0
2

Year Published

1979
1979
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(64 citation statements)
references
References 36 publications
3
59
0
2
Order By: Relevance
“…Indeed, LPS, a major TLR4 ligand, accelerates the disease when administered into BW mice and induces anti-ssDNA and anti-dsDNA Abs and IgG glomerular deposits in normal mice (34). In addition, transgenic mice that constitutively expressed the chaperone molecule gp96 and consequently overexpressed TLR4 on the cell surface developed a lupus-like disease probably due to an enforced TLR4 response to LPS since overexpression of the Tlr4 gene alone was sufficient to induce the disease (26).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, LPS, a major TLR4 ligand, accelerates the disease when administered into BW mice and induces anti-ssDNA and anti-dsDNA Abs and IgG glomerular deposits in normal mice (34). In addition, transgenic mice that constitutively expressed the chaperone molecule gp96 and consequently overexpressed TLR4 on the cell surface developed a lupus-like disease probably due to an enforced TLR4 response to LPS since overexpression of the Tlr4 gene alone was sufficient to induce the disease (26).…”
Section: Discussionmentioning
confidence: 99%
“…Kiyotaki et al (9) demonstrated that peripheral blood lymphocytes from active and inactive SLE patients produced anti-DNA antibodies when stimulated with DNA and T-subsets insensitive to antilymphocyte antibody. Polyclonal stimulator, e.g., bacterial lypopolysaccharide, caused the transformation of normal murine B-cells into anti-DNA antibody forming cells in vitro and in vivo (4,6,7,18). These lines of evidence have shown that B-cells are ready to convert to autoantibody producing cells when some information comes in.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, anti-DNA antibodies were eluted from kidneys of mice injected with LPS. However, the anti-DNA antibodies represented only a fraction of the immunoglobulins deposited in the kidneys, suggesting that other IC were also involved (10).…”
Section: Idiotypic Analysis Of the Immunoglobulins Eluted From Kidneymentioning
confidence: 99%
“…The estimated amount of anti-T15 idiotype antibodies was similar. Discussion A single injection of bacterial LPS in mice has been previously shown (10) to induce glomerular lesions associated with other features of systemic lupus erythematosus, such as the production of anti-DNA antibodies and circulating IC. The glomeruli showed only minimum histologic alterations, but electron microscopy demonstrated electron-dense deposits within the glomerular basement membrane, and immunofluorescence studies showed glomerular deposits of immunoglobulins and complement, suggesting the presence of IC.…”
Section: Idiotypic Analysis Of the Immunoglobulins Eluted From Kidneymentioning
confidence: 99%
See 1 more Smart Citation